Scaunul lui Moise (Mt. 23, 2): O perspectivă istorică și teologică - Bob, Vlad (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
Matthew 23:2-3 is one of the most controversial passages in scripture, and is of particular interest to those seeking to arrive at a correct understanding of the historical context of Jesus’s words. Some scholars have considered the throne of Moses to be just an expression. In the context of chapter 23, however, the seat of Moses has a much broader meaning. The throne of Moses could mean the legacy that Moses leaves from generation to generation, so that the Law received from God on Mount Sinai may be kept, observed, and taught, or interpreted by those who succeed Moses in this sacred dignity. A different perspective on verses 2-3 of chapter 23 is offered by St. Jerome, who compares the seat of Moses with the judgment seat on which the Son of Man or the New Moses will sit at the end of the ages. He will judge all man- kind according to the good deeds criteria. The scribes and Pharisees in chapter 23 ascended the throne of Moses without accepting Christ, the One who is the fulfiller and perfecter of the Law of Moses. They do not have the authority to sit in Moses’ seat. Those who will have this authority will be the disciples of Jesus. They will sit on the thrones of judgment with the Son of Man, the One who will judge all mankind.